Over-the-Counter Access to Oral Contraception: Reproductive Autonomy on Pharmacy Shelves or a Political Trojan Horse? - Dougall, Sarah Mac (Columbia Journal of Gender and Law, 2015)
During the fall of 2014, in what seemed like a change of heart, Republican congressional candidates began calling for a policy that reproductive rights advocates have supported for years. Over-the-counter (“OTC”) oral contraception (“OC”) became these candidates’ way to connect with the women alienated by the Republican Party in recent elections. They emphasized how OTC access would allow women themselves, not employers or the government, to have control over contraceptive decisions. Liberals responded that this new effort was just a Trojan horse—legalizing OTC access would not only increase the actual price tag on OC, but it would also remove OC from the Patient Protection and Affordable Care Act’s extended insurance coverage of contraception. Additionally, reproductive rights advocates noted that it is the FDA, not Congress, that legalizes OTC drugs, and the FDA has not received any applications from drug manufacturers who want to sell OC OTC. In reality, both sides have something of a valid argument. OTC OC would be an important step toward reproductive autonomy for American women. It is also correct, however, that an immediate liberalization of OTC presents several issues, economically, politically, and culturally. Despite these valid critiques, OTC access for OC is a change that is worth the time and effort to move past politics and get it right, for many reasons. Requiring insurance companies and Medicaid to reimburse women for OTC OC purchases is a step toward establishing an accessible market and ensuring corresponding reproductive autonomy for women in the United States, which should accompany legalization of OTC OC.